2013
DOI: 10.1002/pssa.201200374
|View full text |Cite
|
Sign up to set email alerts
|

Radial heteroemitter solar cells based on VLS grown silicon nanowires

Abstract: Silicon nanowires (SiNWs) are an interesting system for the realization of solar cells, as they offer an enhanced light absorption compared to bulk Si. However, due to their large surface, nanowire solar cells suffer from high surface recombination which results in small carrier lifetimes. They therefore need perfect passivation. The use of an amorphous silicon heteroemitter on such structures enables a good surface passivation and therefore enables a higher open circuit voltage (VOC) than in crystalline core–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Therein, the bottom-up method usually uses chemical vapor deposition (CVD) techniques with vapor-liquid-solid (VLS) process for fabricating the dense, high aspect ratio, and vertically aligned SiNWs [1]. Moreover, the formation of pn junction and preparation of SiNWs can be easily prepared together by VLS process [10,11]. However, this method always requires a highly protected quality clean room, and expensive CVD systems lead to an increase of the production cost of material.…”
Section: Introductionmentioning
confidence: 99%
“…Therein, the bottom-up method usually uses chemical vapor deposition (CVD) techniques with vapor-liquid-solid (VLS) process for fabricating the dense, high aspect ratio, and vertically aligned SiNWs [1]. Moreover, the formation of pn junction and preparation of SiNWs can be easily prepared together by VLS process [10,11]. However, this method always requires a highly protected quality clean room, and expensive CVD systems lead to an increase of the production cost of material.…”
Section: Introductionmentioning
confidence: 99%
“…was prepared, and it shows an open circuit voltage of up to 184 mV, a short circuit current density of 1.37 mA cm −2 , a fill factor of 30%, and an efficiency of 0.1%. This indicates that the proposed solar cell model can be realized, and it has good potential for further improvement through optimization of process for the synthesis of Si NWs and fabrication of solar cells .…”
Section: Resultsmentioning
confidence: 90%
“…The reflection ( R ) and transmission ( T ) spectra of Si NWs were measured by a UV–Vis‐NIR spectrometer with integrating sphere, and the absorption spectra were then calculated ( A = 1 − R − T ). The solar cell samples were prepared and characterized as described in the literature .…”
Section: Methodsmentioning
confidence: 99%
“…In the case of a planar sample, the absorption drops to as low as 55% at 400 nm and 70% in the 600 nm wavelength region. 60 Christiansen et al reported their experiment that the nanowires grown on glass substrate have a length of 3-6 µm and diameter in range of 20-100 nm. A strong broadband optical absorption can be observed in the relatively thin Si nanowire films.…”
Section: Nanowire Structures (Bottom-up Method)mentioning
confidence: 99%